Quantum memory with a controlled homogeneous splitting - Hétet, G. (2014)
We propose a quantum memory protocol where an input light field can be stored onto and released from a single ground state atomic ensemble by controlling dynamically the strength of an external static and homogeneous field. The technique relies on the adiabatic following of a polaritonic excitation onto a state for which the forward collective radiative emission is forbidden. The resemblance with the archetypal electromagnetically induced transparency is only formal because no ground state coherence-based slow-light propagation is considered here. As compared to the other grand category of protocols derived from the photon-echo technique, our approach only involves a homogeneous static field. We discuss two physical situations where the effect can be observed, and show that in the limit where the excited state lifetime is longer than the storage time; the protocols are perfectly efficient and noise free. We compare the technique with other quantum memories, and propose atomic systems where the experiment can be realized.